Portfolio Preferences Across Markets: Evidence from Mutual Fund Ownership (International Journal of Banking and Finance, 2012)
This paper is about evaluating and comparing the portfolio preferences of domestic and foreign mutual funds in developed and emerging markets over the period 1998-2007. We find that foreign and domestic mutual funds have some different preferences toward firm characteristics and firm’s information enviroments, and economic development affects the preferences for both types of funds. A country’s characteristics and institutions also influence mutual fund investment decisions when fund managers from their portfolio holdings. Results further show that foreign and domestic mutual funds play a monitoring role in their portfolio firms, but foreign mutual funds cannot monitor firms effectively in emerging markets.